Ilmu Qiro'at: Kajian tentang Konsep, Perkembangan, Hubungannya dengan Ilmu Tajwid, dan Sab'atu Ahruf - Salam, Abdul; Muhasim, Agus; Ade Wahidin; Apud Saputra (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Qiro'at is one of the principal branches of Ulum al-Qur'an that examines the various canonical modes of Qur'anic recitation transmitted authentically (mutawatir) from the Prophet Muhammad (peace be upon him). This discipline plays a significant role in preserving the authenticity of Qur'anic recitation while enriching the understanding of Qur'anic meanings. This study aims to examine the fundamental concepts of Qiro'at, its historical development, its relationship with Tajwid, and its connection with the concept of Sab'atu Ahruf within Qur'anic studies. The research employs a library research method using a descriptive-analytical approach through the examination of classical Islamic literature, scholarly books, and relevant academic journal articles. The findings indicate that the discipline of Qiro'at developed systematically from the time of the Prophet, continued through the era of the Companions, and was later codified by the renowned Imams of Qiro'at. Although closely related to Tajwid, Qiro'at constitutes an independent discipline with distinct objectives and scope. Furthermore, the concept of Sab'atu Ahruf provides the historical foundation for the diversity of Qur'anic recitation, whereas the mutawatir Qiro'at represent the authenticated and authoritative forms of recitation preserved through continuous transmission. Therefore, a comprehensive understanding of Qiro'at remains essential for strengthening both academic and practical approaches to contemporary Qur'anic studies.